PENGGUNAAN MEDIA MESIN PEMBAGIAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI PEMBAGIAN PADA MATA PELAJARAN MATEMATIKA KELAS IV SDN 7 LIMBOTO - Langkadja, Mega Silvia; Fatimah Djafar; Febry Rizki Susanti Kalaka (Al-mujahidah, 2025)
This research is motivated by the low learning outcomes of students in the Division material. This study aims to determine the improvement in the learning outcomes of fourth grade students of SDN 7 Limboto in the Division material in Mathematics. This type of research is classroom action research. The subjects of this study were 18 students of class IV SDN 7 Limboto. The data analysis techniques used in this study were analysis of test results and analysis of observation results. The results of this study indicate that the Application of Division Machine Media can improve student learning outcomes in the Division material. In cycle I, the learning outcomes of students who completed were 8 students 44.4% in the "very poor" category and students who did not complete were 10 students 55.5%. In cycle II, student learning outcomes reached 83.3% in the "good" category. Students who completed were 15 students and 3 students did not complete. This research can be said to be successful if it has reached the success indicator of 75% and this research can be said to be successful with a percentage of 83.3% in the "good" category, so this research needs to be continued in the next cycle.